Effect of Fermentation on the Protein Digestibility and Levels of Non-Nutritive Compounds of Pea Protein Concentrate - Çabuk, Burcu; Nosworthy, Matthew G.; Stone, Andrea K.; Korber, Darren R.; Tanaka, Takuji; House, James D.; Nickerson, Michael T. (Food technology and biotechnology, 2018)
In order to determine the impact of fermentation on protein quality, pea protein concentrate (PPC) was fermented with for 11 h and total phenol and tannin contents, protease inhibitor activity, amino acid composition and protein digestibility were analyzed. Phenol levels, expressed as catechin equivalents (CE), increased on dry mass basis from 2.5 at 0 h to 4.9 mg CE per 1 g of PPC at 11 h. Tannin content rose from 0.14 at 0 h to a maximum of 0.96 mg CE per 1 g of PPC after 5 h, and thereafter declined to 0.79 mg/g after 11 h. After 9 h of fermentation trypsin inhibitor activity decreased, however, at all other fermentation times similar levels to the PPC at time 0 h were produced. Chymotrypsin inhibitor activity decreased from 3.7 to 1.1 chymotrypsin inhibitory units (CIU) per mg following 11 h of fermentation. Protein digestibility reached a maximum (87.4%) after 5 h of fermentation, however, the sulfur amino acid score was reduced from 0.84 at 0 h to 0.66 at 11 h. This reduction in sulfur content altered the protein digestibility-corrected amino acid score from 67.0% at 0 h to 54.6% at 11 h. These data suggest that while fermentation is a viable method of reducing certain non-nutritive compounds in pea protein concentrate, selection of an alternative bacterium which metabolises sulfur amino acids to a lesser extent than should be considered.